2022
DOI: 10.1016/j.phrs.2021.106053
|View full text |Cite
|
Sign up to set email alerts
|

Systemic administration of glucocorticoids, cardiovascular complications and mortality in patients hospitalised with COVID-19, SARS, MERS or influenza: A systematic review and meta-analysis of randomised trials

Abstract: Background Administration of glucocorticoids might reduce mortality in patients with severe COVID-19 but have adverse cardiometabolic effects. Objectives to investigate the effect of systemic administration of glucocorticoids on cardiovascular complications and all-cause mortality in patients hospitalised with respiratory viral infections, including COVID-19, SARS, MERS and influenza. Methods We identified randomised trials published prior to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Mechanisms underlying these beneficial cardiac effects of corticosteroids in COVID-19 patients may include stabilization of the vascular endothelial barrier, which may attenuate perturbations of the cardiac microcirculation, as well as systemic and cardiac anti-inflammatory effects [ 182 ]. Furthermore, a meta-analysis including RCTs evaluating the effect of glucocorticoids in the setting of COVID-19 found that glucocorticoids had no influence on CV events [ 183 ]. Thus, based on the limited amount of data available to date, individual risk assessment before applying corticosteroids, taking into account both the severity of COVID-19 and the presence of HF, may help to optimize the treatment decision and clinical outcome in HF patients.…”
Section: Covid-19 Treatment Strategies and Impact On CV Diseasementioning
confidence: 99%
“…Mechanisms underlying these beneficial cardiac effects of corticosteroids in COVID-19 patients may include stabilization of the vascular endothelial barrier, which may attenuate perturbations of the cardiac microcirculation, as well as systemic and cardiac anti-inflammatory effects [ 182 ]. Furthermore, a meta-analysis including RCTs evaluating the effect of glucocorticoids in the setting of COVID-19 found that glucocorticoids had no influence on CV events [ 183 ]. Thus, based on the limited amount of data available to date, individual risk assessment before applying corticosteroids, taking into account both the severity of COVID-19 and the presence of HF, may help to optimize the treatment decision and clinical outcome in HF patients.…”
Section: Covid-19 Treatment Strategies and Impact On CV Diseasementioning
confidence: 99%
“…Corticosteroids are among the drugs recommended to manage patients with COVID-19 and are widely used for treating other diseases closely related to COVID, such as Severe Acute Respiratory Syndrome and Middle Eastern Respiratory Syndrome (Caiazzo et al 2022 ). This drug class inhibits many inflammation-associated molecules, such as cytokines (IL-6, IFN-γ, and TNF-α), chemokines, arachidonic acid metabolites, and adhesion molecules, besides up-regulating anti-inflammatory mediators (Barnes 2011 ).…”
Section: Pharmacotherapies To Inflammation Treatmentmentioning
confidence: 99%
“…Therefore, prior use of corticosteroids was not associated with improved outcomes in hospitalized COVID-19 patients. 69…”
Section: Treatment Of Cardiovascular Complicationsmentioning
confidence: 99%
“…Therefore, prior use of corticosteroids was not associated with improved outcomes in hospitalized COVID-19 patients. 69 During the acute phase, the use of systemic corticosteroids was shown to decrease mortality according to the Randomised Evaluation of COVID-19 Therapy (RECOVERY) trial, particularly among those patients requiring oxygen therapy. The effect of corticosteroids on cardiovascular complications was assessed in a meta-analysis that found no evidence of beneficial effects in regarding cardiac arrest or ventricular arrhythmias (RR, 1.41; 95% CI, 0.11-18.05), other arrhythmias (RR, 0.83; 95% CI, 0.59-1.16), MI (RR, 0.49; 95% CI, 0.04-5.35) and deep vein thrombosis or pulmonary embolism (RR, 0.53; 95% CI, 0.03-8.77).…”
Section: Treatment Of Cardiovascular Complicationsmentioning
confidence: 99%